REVISITING FIRM VALUE: SUSTAINABILITY REPORTING, CORPORATE GOVERNANCE, AND INTELLECTUAL CAPITAL IN INDONESIA'S ENERGY SECTOR - Mahdalena Alfitri; Arumega Zarefar; Nasrizal (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2026)
Energy companies listed on the Indonesia Stock Exchange exhibited considerable volatility in firm value during 2022–2023, as indicated by movements in stock prices and market-based valuation measures. These fluctuations suggest changing investor evaluations in response to market uncertainty. Accordingly, transparency through sustainability reporting, robust corporate governance mechanisms, and effective resource management become increasingly important in sustaining firm value. This study aims to examine the effect of sustainability report disclosure (measured using the SRDI), corporate governance (proxied by the frequency of board of commissioners’ and board of directors’ meetings), and intellectual capital (measured using the VAIC™) on firm value. The population includes energy sector companies listed on the Indonesia Stock Exchange during the 2021–2023 period. The sample was selected using a purposive sampling method, resulting in 41 companies that met the criteria. Secondary data were obtained from annual and sustainability reports published on the IDX website or the companies’ official websites. The data were analyzed using panel data regression with the assistance of Eviews 12 software. The findings show that sustainability report disclosure, corporate governance, and intellectual capital positively influence firm value. The novelty of this research lies in the reconstruction of theoretical frameworks and the inclusion of a control variable to enhance the robustness of the analysis model.